The establishment and management of a transformative biblical Christain school submitted to a local church - Cerff, Karen (Stellenbosch : Stellenbosch University, 2012)
Education is presently facing the challenge of providing meaningful, relevant education for every youth in the nation, suited to the demands of the next century. The Christian Church has a crucial role to play in establishing and maintaining biblical principles in all spheres of life, including that of education. Since the philosophy of education taught in the schools of one generation, has a major influence on the philosophy perpetuated in the government of the next generation, the urgency and the need for a biblical Christian world view to be upheld in education, are of paramount importance.